(b+1)(b-6)=-12

Simple and best practice solution for (b+1)(b-6)=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (b+1)(b-6)=-12 equation:



(b+1)(b-6)=-12
We move all terms to the left:
(b+1)(b-6)-(-12)=0
We add all the numbers together, and all the variables
(b+1)(b-6)+12=0
We multiply parentheses ..
(+b^2-6b+b-6)+12=0
We get rid of parentheses
b^2-6b+b-6+12=0
We add all the numbers together, and all the variables
b^2-5b+6=0
a = 1; b = -5; c = +6;
Δ = b2-4ac
Δ = -52-4·1·6
Δ = 1
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$b_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$b_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1}=1$
$b_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-5)-1}{2*1}=\frac{4}{2} =2 $
$b_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-5)+1}{2*1}=\frac{6}{2} =3 $

See similar equations:

| 5j+-17=13 | | 1/4(-2v-24)=-3v-6 | | 3(x+1)+x=4(x+5)-13 | | –0.6=–0.2(g+–4) | | 1.1x=40 | | 49-0.3x=0.4+14 | | 102+x+43=180 | | 3(2q−1)=8q−5 | | 19x=-380 | | 8*2h=1÷ | | (2x+3)(x-11)(x/3+7)=0 | | 2-4x=2+2x-6x | | 2824=+x | | 5x^2+40x+18=-47 | | 3x-6+4=-2 | | -4x=12-20 | | 0.1x+x=40 | | 120+2x+x=360 | | 80/10=8+4m/3 | | 4(2x+3)+2=30 | | D=11,d+3 | | 47=8j+14 | | 9x+10=-10x+10 | | (x/6)+(3/5)=4 | | 9x+10=-10x+109x+10=-10x+10 | | -5x+10-4x=-8 | | -10=x+7/3 | | 4/6=2u/42 | | y2–13y+12=0 | | x/6+3/5=4 | | 42=8x-24 | | 7x+18,10x+9=180 |

Equations solver categories